Emerging technologies to enhance starch performance: ozone, ultrasound and irradiation - Silva, Nanci Castanha da (2020)
Starches are widely used in several industrial products and processes. Each application, however, requires different functionalities, which may be not presented by native starches from commercial sources. To work around this issue, two approaches can be used: (1) exploring non- modified starches, especially from unconventional sources and (2) exploring different starch modification techniques. In the present Thesis, both approaches were investigated, with the main objective of enhancing the performance of starches for different applications. In the first part of the Thesis, focused on the use of starches in their native form, besides the characterization of a unconventional botanical source of starch (arracacha root), the processing of starches under non-standard conditions was also explored. In relation to the arracacha starch, the obtained functional properties were very promising from an industrial point of view. Also, by changing the processing conditions, it was shown that it is possible to improve the performance of native starches without the need of modifying them. However, despite bringing a \"natural\" claim to processed foods, the use of native starches may still be limited for some applications. Therefore, in the second part of the Thesis, three different emerging technologies for starch modification were explored: ozone, ultrasound and irradiation. These techniques were selected because they have some advantages over those traditionally used in the industry, such as being more efficient, safer and/or more environmentally friendly. Among the technologies here explored, ozone proved to be a versatile and efficient technology at the evaluated conditions. Each ozonation condition, combined with different starch sources, resulted in distinct functional properties, boosting the possibilities of application for the analysed starches. On the other hand, the ultrasound technology only presented measurable effects when combined with the ozone technology, at the conditions here evaluated. Finally, considering the irradiation technology, it proved to be an efficient and highly penetrating process, resulting in different possibilities of application for the evaluated starches. In all cases, mechanistic discussions were performed in order to correlate the starch structure, its modification using different processes conditions, the obtained properties and possible applications. In conclusion, we highlight that the use of modification processes brings a broader range of applications for starches. However, the particularities and limitations of each modification process need to be considered before its selection.